Bibliometric Analysis of Auditor Switching Development with Vosviewer - Asti Sri Anisa; Rachmat Agus Santoso; F. Fitriana (Manunggal Halim Jaya, 2026)
The decision of a company to switch auditors, known as auditor switching, is a significant issue in the accounting field as it relates to auditor independence, regulatory frameworks, and the dynamics of auditor-client relationships. This study analyzes the development of auditor switching literature using a bibliometric approach based on 103 articles indexed in Scopus from 1988 to 2025. Utilizing VOSviewer software, the research identifies publication trends, core journals, and four main keyword clusters that reflect key research focuses: regulation, internal company conditions, financial pressure, and managerial motivation. The findings reveal a steady increase in publications, peaking in 2019. These results provide a comprehensive overview of the auditor switching research landscape and offer directions for future studies.